ANALISIS POTENSI PAJAK DAERAH DI KOTA YOGYAKARTA - Dedy Haning; Wirawan Endro Dwi Radianto (Jurnal Riset Akuntansi dan Keuangan, 2005)
Local tax become more important since the autonomy program released around 1999. Local authority of Yog,,akarta, which has fewer natural resources, is pushing the local tox revenue in order to manage the city.  This study investigates the role of local tec on Yogtakarta city local tax revenue. Secondary data was used from /998 to 2003. It covers all the local tax in Yogtakarta city that is based on Local Tax Act 34/2000 of Yogtakarta. Several variables are used namely collection ratio, growth, level of contribution and potential matrix of local tax. Study proved that fficiency and growth of local tax decreased and potential matrix steady.Keywords: Local tax, Local tax revenues